Avaliação do tratamento de fissuras anais com a isossorbida tópica a 1% - Prudente, Ana Carolina Lisbôa (2010)
Chronic anal fissures are benign, painful, found deep ulcers in the anal canal. Affecting young adults and occur especially by the trauma of hard stools, the sphincter hypertonia and poor vascularization in the anterior and posterior regions of the anus. Its main symptom is pain evacuation. Surgical treatment is most effective with high cure rates, but with significant adverse effects such as later anal incontinence. The option of conservative treatment is growing, has managed to decrease temporary the pressure at rest (PREP) and increased blood flow to the anal canal, healing large number of lesions without muscle damage. In order to evaluate the treatment of chronic anal fissure with isosorbide (ISO) 1% topical has conducted a clinical trial, double-blind study in patients enrolled in the service of coloproctology Federal University of Sergipe, in the period of one year. We studied 24 patients, distributed as follows: 14 in group 1 cream isosorbide, and 10 in group 2 placebo. We evaluated the behavior of the PREP, pain relief and degree of wound healing with and without ISO. The results showed that the patients ages ranged from 21 to 69 years, the cleft affects more women and the predominant symptom was pain. Constipation was observed in 58.3%. As for pain, lower intensity was obtained in group 2, but without significance. The healing after 60 days was similar in both groups (50%). The profile of the average PREP 30 and 60 days, there was a decrease in the standard in both groups, but without statistical significance. It was observed that patients cured were those with the greatest reduction in PREP. It was concluded that the ISO did not alter the response pattern gauge, however there was significant clinical improvement in both groups. The healing rate was similar in both groups.